Age and productivity: Sector differences? - Christian Göbel; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
In most industrialised countries, the workforce is ageing rapidly. If ageing workforces affect sectors differently, the total impact of ageing will depend on the industrial structure of an economy. This paper measures the impact of changes in the age structure of establishments on productivity using representative linked employeremployee panel data. We argue that establishment age-productivity profiles might differ for various reasons. For example, the importance of physical strength and possibilities to compensate deficits in skills differ between sectors. We investigate differences in the age-productivity profiles between the (metal) manufacturing and services sectors. However, in our preferred specification that controls for several potential sources of estimation biases, we find no significant differences in the ageproductivity profiles between these sectors.
Keywords: J11; J14; J21; 330; Ageing workforce; age; productivity; linked employer employee data; sectors